2020
DOI: 10.1002/pbc.28827
|View full text |Cite
|
Sign up to set email alerts
|

No increase in psychosocial stress of Dutch children with cancer and their caregivers during the first months of the COVID‐19 pandemic

Abstract: We studied the psychosocial impact of the start of the COVID-19 pandemic on Dutch children with cancer in outpatient care and their caregivers (n = 799) using regular monitoring and screening outcomes. No differences were observed between the pre-COVID-19 and early-COVID-19 periods in health-related quality of life and fatigue of children. Fewer caregivers were distressed during the COVID-19 period than pre-COVID-19. In conclusion, the additional stress of COVID-19 did not deteriorate psychosocial functioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 26 publications
6
46
1
Order By: Relevance
“…Many studies aim to predict how lockdown measures will flatten the pandemic curve, but few studies focus on the psychosocial impacts of these interventions on children and their families [5,[45][46][47][48][49][50][51]. As public health experts focus on reducing the spread of COVID-19 infections, it is imperative that they also focus on addressing the psychosocial needs of children.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies aim to predict how lockdown measures will flatten the pandemic curve, but few studies focus on the psychosocial impacts of these interventions on children and their families [5,[45][46][47][48][49][50][51]. As public health experts focus on reducing the spread of COVID-19 infections, it is imperative that they also focus on addressing the psychosocial needs of children.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for this finding may be that these children are more often confronted with stressful events that directly affect their physical health and restraints in daily life due to the management of their disease. As a result, children may have developed more adaptive coping strategies 21,22 . In addition, one could speculate that the COVID-19 pandemic lockdown induced changes in daily life might be less invasive for some of these children as home schooling and carefully taking care of one's physical health may be part of life already 21 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, children may have developed more adaptive coping strategies 21,22 . In addition, one could speculate that the COVID-19 pandemic lockdown induced changes in daily life might be less invasive for some of these children as home schooling and carefully taking care of one’s physical health may be part of life already 21 . Likewise, they may be more used to having online contact with friends, which may explain their higher reported Peer Relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has made parents of children with cancer already experiencing high levels of stress extremely worried about the possible consequences of cancer and the outbreak [ 25 ]. Additional psychosocial stress may reduce their QOL and increase fatigue [ 26 ]. A study conducted in the United Kingdom showed that parents with children with cancer believe that their children are at a higher risk of infection compared to their healthy peers [ 27 ].…”
Section: Introductionmentioning
confidence: 99%